Husband's Legal Responsibility for the Rights of His Wife and Children Post-Divorce - Mochamad Nurdin; Ahmad Zaini Muhlis; Euis Nurasiah Jamil (al-Afkar, Journal For Islamic Studies, 2024)
When a divorce occurs between a husband and wife, it creates obligations that must be obeyed by a husband and wife, and these obligations include the former husband being obliged to provide a gift that must be given to the former wife who has been divorced. This article aims to examine the husband's responsibilities towards his wife and children after divorce. The existence of divorce does not mean the release of the husband's responsibility to provide responsibilities to the ex-wife, be it iddah maintenance, mut'ah, and child maintenance, provided that it is in accordance with the husband's ability. This research is a type of empirical juridical research, or called field research, which examines the applicable legal provisions and what happens in reality in society. This research is a type of empirical juridical research, or called field research, which examines the applicable legal provisions and what happens in reality in society. Empirical juridical research is legal research on the enactment or implementation of normative legal provisions in action on each specific legal event that occurs in society. The results of this study indicate that the husband is responsible for the former wife and children after divorce in the Religious Court, that the former wife must receive maintenance in the form of mut'ah, iddah maintenance, madhiyah maintenance, and for children's rights or child maintenance. The husband is obliged to provide maintenance to the child in the future, and the prosecution system is every month until the child is 21 years old or has grown up. This policy is carried out to provide justice for wives who are divorced by their husbands.